Revolution of mobile banking applications towards banking customers in northern region, Malaysia / Nur Alia Syahirah Zahari, Dr. Nurul Labanihuda Abdull Rahman and Hasyeilla Abdul Mutalib - Zahari, Nur Alia Syahirah; Abdull Rahman, Nurul Labanihuda; Abdul Mutalib, Hasyeilla (Universiti Teknologi MARA, Kedah, 2024)
Mobile banking services are increasingly common in Malaysia. Many people are drawn to using mobile banking in their daily lives because of its benefits for banking customers. Customers have the option of making online transactions rather than doing so in person at the bank counter. Banking customers are able to make a transaction with just one click from their gadgets in the information technology (IT) era. The term mobile banking applications refers to a mobile service that enables quick and easy money transactions from one account to another account. This paper seeks to study the determinants of the continuous intention of mobile banking applications from banking customers' perspectives in the Northern Region, of Malaysia. A quantitative approach was used in this study. Questionnaires were used to collect the data from all respondents through Google Forms. The respondents were banking customers from the Northern Region, Malaysia who used mobile banking applications with a number of samples of 384 respondents for this study in order to properly reflect the population and they were selected using stratified random sampling. The Partial Least Square (SmartPLS) will be used to evaluate the research data. Finally, this study can be applied and extended to determine the determinants of continuous intention on mobile banking applications in other countries.